Training on Making Powerpoint Learning Media for Teachers at SDN 9 Singkawang - Erdi Guna Utama; Kamaruddin Kamaruddin; Dewi Mariana; Mertika Mertika (International Journal of Public Devotion, 2019)
This service activity aims to increase teacher understanding and knowledge of the importance of learning media in learning activities in elementary schools (SD). In addition, this program also trains SDN 9 Singkawang teachers in designing and making instructional videos using powerpoint-based media. The specific target to be achieved is to increase teacher creativity in designing and using video learning media so that learning in schools will be more contextual. The method used in the implementation of this Community Service is in the form of counseling, training, and question and answer methods. This activity begins with observations in schools and related institutions / agencies in the first week. This was followed by core activities at SDN 9 Singkawang. The core activity is in the form of socialization activities about making instructional videos using powerpoint-based media for elementary school teachers at SDN 9 Singkawang. The target audience in this activity were elementary school teachers at SDN 9 Singkawang. This activity has been able to increase teacher knowledge about the urgency of instructional media and the development of forms of instructional media, especially those related to technological developments. This activity has also been able to improve the ability of teachers to operate computers or laptops, including loading powerpoint media and combining them.